SME failures under large liquidity shocks: An application to the COVID-19 crisis - Pierre-Olivier Gourinchas; Sebnem Kalemli-Ozcan; Veronika Penciakova; Nicholas Sander (Bank of Canada, 2023)
We study the effects of financial frictions on firm exit when firms face large liquidity shocks. We develop a simple model of firm cost-minimization that introduces a financial friction that limits firms' borrowing capacity to smooth temporary shocks to liquidity. In this framework, firm exit arises from the interaction between this financial friction and fluctuations in cash flow due to aggregate and sectoral changes in demand conditions, as well as more traditional shocks to productivity. To evaluate the implications of our model, we use firm-level data on small and medium-sized enterprises (SMEs) in 11 European countries. We confirm that our framework is consistent with official failure rates in 2017-2019, a period characterized by standard business cycle fluctuations in demand. To capture a large liquidity shock, we apply our framework to the COVID-19 crisis. We find that, in the absence of government support, SME failure rates would have increased by 6.01 percentage points, putting 3.1 percent of employment at risk. Our results are consistent with the premise that financial frictions lead to inefficient exit as, without government support, the firms failing due to COVID-19 have similar productivity and past growth to firms that survive the COVID-19 crisis.
Keywords: D21; D22; E65; H81; 330; Firm dynamics; International topics; Coronavirus disease (COVID-1